Pembuatan Crude Biodiesel Dari Cpo BER FFA Tinggi Dengan Menggunakan Katalis ZnO Sintesis - Martin, Intan Fitra; Helianty, Sri; Yusnimar, Yusnimar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Biodiesel is an alternative fuel that becoming worldwide attention as renewable energy which could replace diesel fuel in compression ignition engines. It can be produced from CPO which has a high free fatty acid through the process called transesterification was catalyzed by zinc oxide (ZnO) catalyst. Heterogeneous catalyst such ZnO was promising candidate which has various advantages such as the easy catalyst separation from the reaction mixture, product purification and the reduction of environment pollutants. The purpose of this research is to synthesis ZnO catalyst by natrium oxalate precipitation. The crude palm oil has free fatty acid as such as 8,36%, so CPO conversion was conducted by esterification then transesterification reactions. The esterification reaction was occured at temperatures 65oC with H2SO4 catalyst as much as 1% w/w of oil. The transesterification reaction was occured at temperatures 65oC; with the molar ratio of crude palm oil to methanol were 1:6, 1:12, 1:18; concentration of ZnO catalysts were 0,3%, 0,4% and 0,5%; reaction time was 60 minutes. ZnO catalyst exhibited good activity in the biodiesel production with the yield of FAME above 98% after 1 hour of reaction with the molar ratio of methanol oil 1:18 and ZnO catalyst concentration of 0.5% w/w of oil. The produced crude biodiesel has density 878,5 kg/m3, viscosity 5,7 mm2/s, flash point 165oC, acid value 0,75 mg-KOH/g-biodiesel and alkyl ester content 97,2%.Keywords : crude biodiesel, crude palm oil, esterification, transesterification, ZnO.